GAMBARAN FAKTOR RISIKO KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS BANJARNEGARA 1 TAHUN 2021 - Bayu Suseno; Suryawati Rima Pratiwi (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2022)
Pneumonia is a health problem and the largest contributor of death in infants. The beginning of the year 2021, the discovery of cases in January - April achieve the 34 cases in toddlers in tthe health center Banjarnegara 1 Banjarnegara Regency. The purpose of this study is to describe an overview of the factors of the occurrence of pneumonia, especially in infants in the work health center Banjarnegara 1 Banjarnegara Regency in 2021. This research type is descriptive with Cross Sectional approach. This research was conducted by the method of interview to caregivers of toddlers patients with pneumonia. This research was conducted in the month of June of the year 2021 in the working area of Puskesmas Banjarenagara 1. The subject under study, namely the whole house in which there is a toddler under the age of 6 years with a large sample of 34 respondents. The sampling technique used is total sampling. The processing of data using univariate analysis in the form of a table. The results showed that the proportions nutritional status of patients with pneumonia in the dominance of a toddler good nutritional status (94,1%), age of patients with pneumonia most of 1-4 years (the 61.8%), the habit of the members of the smoking most of which are not smoking (58,8%), the knowledge of caregivers about the pneumonia most of the low ( 79,4%), air ventilation most eligible (79,4%), the lighting in the room most qualified (82,4%), and the residence of habitation eligible (79,4%). Based on the research results, suggestions are proposed is to implement the behavior of the healthy and clean living such as not smoking in the house or near a toddler, increase outreach activities to the community regarding these terms of home healthy so that preventive measures can be done.